Theory and Practice of Setting Flexible Working Time for Vulnerable Categories of Workers (EUROPEAN AND ASIAN LAW REVIEW, 2025)
The article is devoted to the legal regulation of the flexible working time regime and the problem of its application in practice. The author provides a brief analysis of the norms of labor legislation in the post-Soviet space and the countries of the Eurasian Economic Union in order to identify the features of this working time regime and solve the emerging dilemmasin the process of its establishment.
Keywords: employment; working time; flexible work schedule; vulnerable category of workers